Workplace skills and teacher competency from culinary arts students’ perspectives - Mohamed, Hanis; Mohd Puad, Mohd Hazwan; Mat Rashid, Abdullah; Jamaluddin, Rahimah (Universiti Putra Malaysia Press, 2021)
Workplace skills are essential skills needed by graduates today to fulfill the demands of employers. Employers in the hospitality industry are looking for well-prepared Culinary Arts graduates that possess adequate training and are equipped with workplace skills to fill up positions in the job market. Apart from skills, teacher competency impacts the acquisition of knowledge and workplace skills among Culinary Arts students and contributes to the issue of unemployment. This study aims to differentiate workplace skills and teacher competency based on gender, socio-economic status, as well as academic and vocational achievements of Culinary Arts students. Furthermore, the relationship between workplace skills and teacher competency is assessed. This correlational study was conducted at Malaysian vocational colleges offering 2-year Culinary Arts programs involving 198 final year students. A 5-point Likert-scale questionnaire was used for data collection. The findings demonstrated that the students’ workplace skills and perception of teacher competency were at a moderate level. No significant differences were noted based on gender, socioeconomic status, as well as academic and vocational achievements. Teacher competency and workplace skills were correlated moderately and positively. This study provides a basis and serves as a reference to the Technical and Vocational Education and Training practitioners to design a curriculum for vocational college students in improving the acquisition of students’ workplace skills. Teachers are recommended to play an active role in efficiently integrating workplace skills in the learning process to enhance their competencies.